Surface ionisation of molecular H2 and atomic H Rydberg states at doped silicon surfaces - Sashikesh, G; So, E; Ford, MS; Softley, T (Taylor and Francis Ltd., 2014)
The detection of ions or electrons from the surface ionisation of molecular H2 and atomic H Rydberg states incident at doped Si surfaces is investigated experimentally to analyse the effect of the dopant charge distribution on the surface-ionisation processes. In both experimental studies, the molecular H2 and atomic H Rydberg states are generated via two-colour vacuum ultraviolet - ultraviolet (VUV-UV) resonant excitation. For H2, various Stark states of the N+ = 2, n = 17 manifold are populated in the presence of an electric field. The variation of the observed surface-ionisation signal with surface dopant concentration and type, shows similar characteristics for all the Stark states. A comparison is made between these ion-detected surface-ionisation profiles and those obtained via electron detection. Different trends as a function of dopant concentration and type are observed for the two cases, explained by the greater effect of surface charges on the post-ionisation ion trajectory compared to the electron trajectory. For the atomic-H Rydberg states with principal quantum number populated in the absence of a Stark field, the observed behaviour is similar to the interaction of molecular H2 Rydberg states at the same surfaces, and these measurements confirm that the observed effects are attributable to the nature of the target surface rather than the specific atomic or molecular Rydberg species.